Simultaneous determination of As, Bi, Sb, Se, Sn and Te in lead alloy using flow injection-hydride generation-inductively coupled plasma mass spectrometry. Issue 37 (7th September 2016) - Soares, J.; Nunes, M. A. G.; Flores, E. M. M.; Paniz, J. N. G.; Dressler, V. L.
Abstract : A method based on flow injection-hydride generation-inductively coupled plasma mass spectrometry (FI-HG-ICP-MS) for the determination of trace amounts of As, Bi, Sb, Se, Sn and Te in lead alloys was developed. Abstract : A method based on flow injection-hydride generation-inductively coupled plasma mass spectrometry (FI-HG-ICP-MS) for the determination of trace amounts of As, Bi, Sb, Se, Sn and Te in lead alloys was developed. The analytical parameters for the analyte determination were 0.60% m/v sodium tetrahydroborate (2.6 mL min −1 ); 90 μL sample volume and 1.25 L min −1 carrier gas (Ar) flow rate. Hydrochloric acid (6.0 mol L −1 for As, Bi, Se and Te and 0.1 mol L −1 for Sb and Sn) was used as sample carrier at 7.4 mL min −1 . Three FI systems were developed and consist of a single channel and dual channel, with one and two gas–liquid separators, respectively. The systems with a dual channel permit the simultaneous determination of all elements, by using two reaction conditions. The effect of Ag, Bi, Cu, Pb, Sb and Te, which were the main elements present in the sample, on the analyte determination was evaluated. With the use of optimized experimental conditions, all elements could be determined by external calibration. The LOQ were 0.14, 0.02, 0.03, 0.02, 0.02 and 0.02 μg g −1 for As, Bi, Sb, Se, Sn and Te, respectively, and the RSD was 8% or lower for five consecutive measurements of a sample solution. Analyte recoveries were in the range of 94 to 101% and the results were in good agreement with those obtained by ICP OES. The method was applied to determine the analytes in lead alloy samples used in automotive battery manufacture, with a sample throughput of 10 determinations h −1 .